Framework Pengembangan SDM Tendik di FSRD Universitas Sebelas Maret Berbasis Innovation Capability - Muh Safrudin; Sigied Himawan Yudhanto (SAP (Susunan Artikel Pendidikan), 2023)
This research is a conceptual framework design that serves as a guide in human resource development and HR development management for educational staff at the Faculty of Art and Design, Sebelas Maret University, Surakarta. The framework concept itself was obtained by a qualitative method combined with content analysis. The research was carried out from August to December 2022. The results obtained were a framework with performance as a boundary and the framework presented that starting from active management support in participation to intense communication built in groups will have a major influence on the transformation of workforce management education in the form of outcomes that have implications for three main levels, namely the group level, organizational level, and individual level where at each level there are four characteristics that must be met so that in the process stages, towards the final result in the form of innovation capability. Innovation capability has parameters that are described in six stages of HR management which will be three parts input, process and outcome.